2020
DOI: 10.1186/s40635-020-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive care unit ambient sounds on healthcare professionals: results of an online survey and noise exposure in an experimental setting

Abstract: Background Noise levels on intensive care units (ICUs) are typically elevated. While many studies reported negative effects of ICU ambient sounds on patients, only few investigated noise as a factor to influence well-being or performance in healthcare professionals. Methods An online survey in the German-speaking part of Switzerland was conducted to assess how ICU soundscapes are subjectively perceived by healthcare professionals. The questionnaire was answered by 348 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
1
20
0
2
Order By: Relevance
“…The checklists used for identifying or grouping sound sources is also unique to each paper and often difficult to replicate due to a lack of details. The checklists may be made up of more generalized groups ( 2 , 9 ), while others may use more detailed lists or include additional precisions per group ( 3 , 4 , 9 , 25 ). As such, it is relevant to the field to tackle this lack of consistency so that progress can be made in reducing high sound pressure levels, an issue that concerns hospitals worldwide ( 1 , 2 , 4 , 9 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The checklists used for identifying or grouping sound sources is also unique to each paper and often difficult to replicate due to a lack of details. The checklists may be made up of more generalized groups ( 2 , 9 ), while others may use more detailed lists or include additional precisions per group ( 3 , 4 , 9 , 25 ). As such, it is relevant to the field to tackle this lack of consistency so that progress can be made in reducing high sound pressure levels, an issue that concerns hospitals worldwide ( 1 , 2 , 4 , 9 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive Care Unit (ICU) professionals are exposed to a lot of noise in their ICU work environment [ 1 , 2 ]. This raises concerns as noise has been found to have a negative impact on cognitive performance in other occupational settings [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…patient alarms, coughing, yelling, preparing medication, and equipment sounds), is defined as noise when there is a negative perception associated to it [ 6 , 7 ]. This is the case for ICU professionals, as they perceive the aforementioned sounds in their environment as being negative [ 2 ]. Heightened noise levels in ICUs have subjectively been found to induce annoyance and stress, decrease overall well-being, and reduce work performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complaints due to high noise levels across the various wards and ICU were not different from what has been revealed in previous studies. A study found that both children and parents have experienced poor sleep in hospital wards than home with a sleep e ciency level of 77% versus 83.2% and 77.1% versus 88.9%, respectively following hospital exposure levels of 48.6 dB (A)(Bevan et al, 2019).Response from 348 participants shows that sound pressure levels in the ICU induce stress and affect occupant's well-beings including contributing to reduction in comfort levels(Schmidt et al, 2020). Apart from annoyance, noise exposures have been associated with an increased number of awakenings, and a decrease in sleep durations caused by frequent rapid eye movement in a typical ICU room during night times(Wallace et al, 1999).…”
mentioning
confidence: 99%